2016
DOI: 10.1021/acs.jpca.6b03950
|View full text |Cite
|
Sign up to set email alerts
|

Gauge-Origin Independent Calculations of the Anisotropy of the Magnetically Induced Current Densities

Abstract: Gauge-origin independent current density susceptibility tensors have been computed using the gauge-including magnetically induced current (GIMIC) method. The anisotropy of the magnetically induced current density (ACID) functions constructed from the current density susceptibility tensors are therefore gauge-origin independent. The ability of the gauge-origin independent ACID function to provide quantitative information about the current flow along chemical bonds has been assessed by integrating the cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 61 publications
(185 reference statements)
2
50
0
Order By: Relevance
“…These results pointed to limited applicability of the ACID method. The same view was upheld by Sundholm et al who had experienced first‐hand that ACID could lead to wrong results. It should be noted that Herges et al in 2001 had published ACID results for silabenzene, wrongly representing it as nonaromatic 15b,c.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results pointed to limited applicability of the ACID method. The same view was upheld by Sundholm et al who had experienced first‐hand that ACID could lead to wrong results. It should be noted that Herges et al in 2001 had published ACID results for silabenzene, wrongly representing it as nonaromatic 15b,c.…”
Section: Introductionmentioning
confidence: 99%
“…It allows one to visualize conjugated domains (separately for diamagnetic and paramagnetic contributions) and to carry out numeric evaluation of current strength by integration of the current flow along specific bonds, thus depicting electron-delocalization pathways. Rightly criticizing the ACID method, the authors [17][18][19] have demonstrated that the results of numerical aromaticity evaluations obtained using GIMIC method agree well with the data of other aromaticity descriptors and with general chemical conceptions, especially in cases where the ACID method had failed. [17] In this article, we present and discuss the results obtained by the GIMIC method for the carbene analogs of types 1 and 2 as well as 3 Tables 1-3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not the case as obtained from the current strength calculation. In this context, it is vital to note previous calculation by Fliegl et al, which shows that for nonaromatic and aromatic molecule the value ΔJ21/2 falls in the range (2.4‐3.5), whereas in cyclobutadiene (antiaromatic) it is 5.5 nA/T (the highest) at the B3LYP/def2‐TZVP level of theory. Thus, the ACID cross‐sectional area does not confer the electron flow through the area under investigation.…”
Section: Resultsmentioning
confidence: 93%
“…This seems to be going around in circles. Fliegl et al concluded that ACID method does not provide extra information about the aromaticity of a hollow polyhedron carbon molecule, besides the information already obtained from J ( r ) maps . Moreover, it has been recently showed that the ACID method is missing the antisymmetric part of ℐ ( r ) which is essential to properly describe the electron delocalization .…”
Section: Introductionmentioning
confidence: 99%